L n - proper Functions - Al-khafaji, Adnan (University of Thi-Qar Journal of Science, 2010)
In this paper, the concepts of L n - proper Functions are defined depending on the definition of L - spaces which was presented by (Kelley, J.C. : 1963 in [3]) and the concept of Proper Functions which was presented by (Bourbaki, N. in [1]). Also we used this concept to study some theorems which are related to the concept of proper Functions.